Institucionalização da Gestão Escolar no Brasil: em foco as primeiras décadas do século XX (1911-1950) - Lopes, Natalina Francisca Mezzari; Ribeiro, Ricardo [UNESP] (My University, 2014)
This work aims to investigate the institutionalization of management processes in the legislation of the Brazilian education. For this study was considered the first decades of the twentieth century (1911-1950). The laws of Brazil in the early Republic were derived from tradition or forged by the great legislators. In turn, the tradition is inserted in the power of social organization that is preserved, in a more forceful manner, through the norms and rules. With this assumption, the study chose the Rivadávia and Carlos Maximiliano Reforms, both of the beginning of the century, and the Organic Laws of Teaching, granted by the government in this period, to understand how legislation institutionalized the role of the director in basic education in this context history. The reflections presented introduce historical elements that demonstrate actions and relationships that remain in the form of habits in the school managements. These institutionalized elements contribute to the debate about the political and pedagogical difficulties pointed out by scholars and professionals, related to the promotion of democratic management in the public school.

Este trabalho visa investigar a institucionalização dos processos de gestão na legislação da educação brasileira. Para esse estudo delimitou-se as primeiras décadas do século XX (1911 – 1950). As leis no início do Brasil República foram derivadas da tradição ou forjadas pelos grandes legisladores. Por sua vez, a tradição representa o poder inserido na organização social que se conserva, de forma mais contundente, através das normas e regras. Com esse pressuposto, o estudo elegeu as Reformas Rivadávia e Carlos Maximiliano do início do século e as leis orgânicas do ensino para compreender como, neste contexto histórico, a legislação institucionalizou a função do diretor na educação básica. As reflexões apresentadas introduzem elementos históricos que demonstram ações e relações que permanecem em forma de hábitos nas gestões escolares. Estes elementos institucionalizados contribuem para o debate em torno das dificuldades políticas e pedagógicas sinalizadas por estudiosos e profissionais da área, relacionadas à promoção da gestão democrática na escola pública.
The integration of information and communication technologies in schools: the political pedagogical project in this context
Keywords: School management; School director; Educational legislation; Gestão escolar; Diretor Escolar; Legislação Educacional